Digital Transformation Of Islamic Educational Leadership: Managerial Challenges In Managing Madrasah Artificial Intelligence (AI) Based In The Era Of Society 5.0 - Febrineng; Firman (International Journal of Technology and Education Research, 2026)
Digital transformation in the era of Society 5.0 present fundamental challenges for leadership Islamic education, in particular in context management of madrasas that are starting integrated with Intelligence Artificial. Problematics the main thing that comes to the fore is gap digital competence of madrasah principals, dilemma Islamic ethics in taking decision based algorithm, limitations infrastructure technology that creates digital divide, as well as resistance cultural-organizational from community Islamic education is worried will erosion values tradition and spirituality. Research This use method studies literature with analyze various literature scientific. Research results disclose that paradigm leadership Islamic education must shift from management administrative conventional going to leadership integrative that combines spiritual wisdom with digital skills, where the principal plays a role as a visionary digital- murabbi. Challenges digital competence and Islamic ethics become issue crucial that demands existence balance between AI utilization and principles Maqashid Syariah. Adaptive strategies are needed covers management infrastructure technology in a way contextual, ethical student data security, and​ development integrated AI curriculum with the values of monotheism. Meanwhile that, the gap implementation and resistance organizational need approach diplomatic and policy - based change culture. In conclusion that digital transformation of leadership Islamic education is an inevitability that must be responded to with strengthening digital literacy, compilation guide ethical the use of AI in madrasas, as well as development system management learning appropriate AI- based with context local and values Islam.